The prevalence and impact of childhood sexual abuse on HIV-risk behaviors among men who have sex with men (MSM) in India. (December 2016) - Tomori, Cecilia; McFall, Allison; Srikrishnan, Aylur; Mehta, Shruti; Nimmagadda, Nymisha; Anand, Santhanam; Vasudevan, Canjeevaram; Solomon, Suniti; Solomon, Sunil; Celentano, David
Abstract Background Childhood sexual abuse (CSA) is a significant global public health problem, which is associated with negative psychosocial outcomes and high-risk sexual behaviors in adults. Men who have sex with men (MSM) often report higher prevalence of CSA history than the general population, and CSA may play a key role in MSM's greater vulnerability to HIV. Methods This study examined the prevalence of CSA history and its impact on the number ofrecent HIV-related risk behaviors (unprotected anal intercourse, high number of male and female sexual partners, alcohol use, drug use, and sex work in prior 6 months) andlifetime risk behaviors and experiences (high number of lifetime male and female sexual partners, early sexual debut, injection drug use, sex work, and intimate partner violence) among 11, 788 adult MSM recruited via respondent driven sampling across 12 sites in India, with additional insights from thematic analysis of qualitative research with 363 MSM from 15 sites. Results Nearly a quarter (22.4 %) of participants experienced CSA, with substantially higher prevalence of CSA in the South and amongkothis (feminine sexual identity). Qualitative findings revealed that older, trusted men may target young and, especially, gender nonconforming boys, and perpetrators' social position facilitates nondisclosure. CSA may also initiate further same-sex encounters, including sex work. In multivariable analysis, MSM who experienced CSA had 21 % higher rate ofrecent (adjusted rate ratio [aRR = 1.21], 95 % confidence interval [CI]: 1.14–1.28), and 2.0 times higherlifetime (aRR = 2.04, 95 % CI: 1.75–2.38) HIV-related behaviors/experiences compared with those who did not. Conclusion This large, mixed-methods study found high overall prevalence of CSA among MSM (22.4 %), with substantially higher prevalence among MSM residing in the South and among more feminine sexual identities. Qualitative findings highlighted boys' vulnerabilities to CSA, especially gender nonconformity, and CSA's role in further sexual encounters, including sex work. Additionally, CSA was associated with an elevated rate ofrecent, and an even higher rate oflifetime HIV-related risk factors. Our results suggest an acute need for the development of CSA prevention interventions and the integration of mental health services for MSM with histories of CSA as part of HIV-prevention efforts.